Family Income and Health Insurance as Factors Related to Family Response to Acute Coronary Syndrome Attack - Servasius To’o Jala Mulu; Titin Andri Wihastuti; Dhelya Widasmara (International Journal of Science and Society, 2020)
Response to attack Acute Coronary Syndrome (ACS) significantly contributes to the incidence of complications and death in ACS patients. This response is concerned with making decisions regarding emergency care. The family is one of the decision makers regarding emergency care for ACS patients. Economic problems and the ownership of health insurance can cause a poor response. Analytic observational design, cross sectional was used in 104 patient families (parents / husband / wife / children) who are in charge of care for ACS patients at the Ende Regional General Hospital using a modified Acute Coronary Syndrome Response Index questionnaire. Less response was found in 42.3% of respondents. There was a significant relationship between response and family income (P = 0.000, OR = 0.599) but not with health insurance ownership (P = 0.359; OR = 0.090). Response is less closely related to economic problems experienced even though the patient has been insured. Therefore, it is important to develop strategies to increase the response (knowledge, attitudes and beliefs) of families related to SKA, especially in low-income groups. This will help them speed up decision making when SKA's re-attack occurs.